The responsibilities of the dapartment chairmen of two selected teachers colleges in Manila a comparative study - Chantraroj, Chalermchai 1944-
All of the 13 department chairmen of the Philippine Normal College (PNC) were responsible for the recruitment of faculty, screening of applicants, interviewing teacher-candidates, sitting with new teachers on the departmental set-up, policies and programs; recommending to the Dean would-be-full-time instructors; providing lesson planning materials to new teachers before the opening of classes; distributing the loads of the faculty in the department; etc. The department chairmen of the National Teachers College have the same job responsibilities as their PNC counterparts in the area of faculty selection, orientation and assignment.